Improving Understanding of Rectangle Perimeter Concepts Using Teaching Aids Through a Realistic Mathematical Approach Grade III students at SD Negeri 4 Napabalano, Muna Regency - Nurnanenci; Sundari Hamid (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to improve students' understanding of the concept of the perimeter of a rectangle using visual aids through a Realistic Mathematical Approach in class III SD Negeri 11 Napabalano, Muna Regency. This research is qualitative in nature. The research data collection technique was carried out by tests, interviews, observations and field notes. The type of data collection used was a class action research type. The results of the study show that learning the concept material and the circumference of a rectangle using visual aids through a Realistic Mathematical Approach can make students relaxed, happy, and not tense in learning. The learning is carried out by: (1) showing objects around which are rectangular and which are not rectangular; (2) students complete the LKS by using the visual aids that have been given; (3) Each group presented the results of their discussion while the other students gave their responses; (4) students construct the perimeter of a rectangle through the teacher's guidance; (5) students solve questions and other realistic problems. So that the provision of learning actions can be concluded that learning using visual aids by applying a realistic mathematical approach can increase students' understanding of the material around rectangles